A prospective evaluation of the availability and utility of the Ambulance Call Record in the emergency department. Issue 2 (13th September 2016) - Cram, Natalie; McLeod, Shelley; Lewell, Michael; Davis, Matthew
Abstract: Objective: To determine how often the Ambulance Call Record (ACR) was available to emergency department (ED) physicians and whether it contained information that changed the ED management of patients. Methods: This was a prospective cohort study of adult patients transported to one of two tertiary care centre EDs. Physicians completed a data collection form for each patient regarding ACR availability and the perceived value of the ACR. This study began shortly after the implementation of a new electronic ACR (eACR) handover process (Round 1). To control for any confounding factors related to this new eACR handover process, the study was repeated 6 months after its implementation (Round 2). Results: Total of 869 forms were collected: 545 in Round 1, and 324 in Round 2. The ACR was available at first physician assessment for 82 (15.7%) patients in Round 1, and 76 (24.4%) patients in Round 2 (Δ8.7%, 95% CI: 3.1%, 14.5%). The ACR was available at some point during patients' ED stay for 154 (28.9%) patients in Round 1, compared to 111 (34.5%) patients in Round 2 (Δ5.6%, 95% CI: 0.0%, 12.1%). When the ACR was available for a patient (n=265), physicians believed that information in the ACR changed their treatment plan in 76 (28.8%) cases. Conclusion: Physicians who review the ACR believe that the ACR contains relevant information that may influence patient management; however, physicians commonly manage patients without reviewing the ACR. Résumé: Objectifs: L'étude visait à déterminer dans quelle mesure les enregistreurs d'appels d'ambulance (EAA) étaient à la disposition des médecins et si les renseignements fournis influaient sur le traitement des patients au service des urgences (SU). Méthode: Il s'agit d'une étude de cohorte prospective, composée d'adultes transportés à l'un des deux SU de soins tertiaires. Les médecins ont rempli, pour chacun des malades, un formulaire de collecte de données relativement à la présence ou non d'un EAA et à la perception de la valeur de ce type d'appareil. L'étude a commencé peu de temps après la mise en œuvre d'un processus de transfert de soins à l'aide d'un nouvel EAA électronique (1 re étape). Six mois après la mise en œuvre du processus de transfert de soins (2 e étape), l'étude a été reprise afin que soit éliminé tout facteur parasite lié à l'utilisation du nouvel EAA électronique. Résultats: Au total, 869 formulaires ont été recueillis : 545 au cours de la 1 re étape et 324 au cours de la 2 e étape. Un EAA était disponible à la première évaluation médicale de 82 (15, 7 %) patients au cours de la 1 re étape et de 76 (24, 4 %) patients au cours de la 2 e étape (écart [Δ] 8, 7 %; IC à 95 % : 3, 1 %-14, 5 %). Par ailleurs, les médecins avaient la possibilité d'écouter l'EAA à tout moment durant le séjour des patients au SU dans 154 (28, 9 %) cas au cours de la 1 re étape et dans 111 (34, 5 %) cas au cours de la 2 e étape (Δ 5, 6 %; IC à 95 % : 0, 0 %-12, 1 %). Enfin, les médecins étaient d'avis que, lorsqu'il était possible d'écouter les EAA (n=265), les renseignements fournis avaient modifié le plan de traitement de 76 patients (28, 8 %). Conclusions: Les médecins qui écoutent les EAA estiment que les appareils fournissent des renseignements utiles, susceptibles de modifier le traitement des patients; toutefois, les médecins traitent généralement les patients sans écouter les EAA.